2004
DOI: 10.1177/000992280404300606
|View full text |Cite
|
Sign up to set email alerts
|

Parental Beliefs and Practices Regarding Early Introduction of Solid Foods to Their Children

Abstract: This study was a cross-sectional survey of primary female caregivers during their child's 4-month well-child visit. Our objectives were to document current caregiver awareness of infant feeding guidelines, and calculate the frequency of and reasons for early introduction of solid foods. Questionnaires were completed for 102 children. Forty-five respondents (44%) introduced solids at less than 4 months of age. Hispanic caregivers, OR 0.2 (0.07-0.9), and those who breastfed (partial or exclusive), OR 0.4 (0.2-0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 17 publications
2
44
1
Order By: Relevance
“…To better understand the potential implication of this sample restriction, we compared our analytic sample with the IFPS II population and observed that our analytic sample was more likely to be older, married, have a high level of educational attainment, higher income, and less likely to participate in WIC (data not shown). Because mothers of lower socioeconomic status are at a higher risk of early solid food introduction, 4,[13][14][15] it is reasonable to think that our sample may underestimate the prevalence of early solid food introduction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To better understand the potential implication of this sample restriction, we compared our analytic sample with the IFPS II population and observed that our analytic sample was more likely to be older, married, have a high level of educational attainment, higher income, and less likely to participate in WIC (data not shown). Because mothers of lower socioeconomic status are at a higher risk of early solid food introduction, 4,[13][14][15] it is reasonable to think that our sample may underestimate the prevalence of early solid food introduction.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3] The early introduction of solid foods is of concern because, developmentally, younger infants (particularly those ,4 months of age) are not prepared for solid foods. 4 In addition, researchers have suggested that early introduction of solids may increase the risk of some chronic diseases, such as diabetes, obesity, eczema, and celiac disease. [5][6][7][8] The early introduction of solids also ends exclusive breastfeeding and has been associated with reduced duration of any breastfeeding.…”
mentioning
confidence: 99%
“…In both the UK and the US, many parents give night-waking as the reason they switched to formula (Douglas & Hill, 2013) and the idea that feeding the infant formula before bed will help the whole family to sleep better is widely accepted (Rosen, 2008). Mothers are advised by peers and family to introduce formula or solid foods to the infant diet in order to promote longer periods of nocturnal sleep (Clayton, Li, Perrine, & Scanlon, 2013;Crocetti, Dudas, & Krugman, 2004). This advice is at odds with WHO and National Health Service (NHS) recommendations to breastfeed exclusively to six months of 3 age (World Health Organization, 2001); although around one-third of women in the UK breastfeed to six months, only 1% do so exclusively (McAndrew et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Medical and public health advocacy groups such as the American Academy of Pediatrics have therefore issued guidelines and recommendations to promote evidence-based practices for immunization, 1,2 breastfeeding, 3,4 and safe sleep behaviors. 5 Although studies have revealed associations between recommendations and maternal infant care practice choices, [6][7][8] adherence to these practices remain below targeted goals. [9][10][11][12][13] Advice received by mothers from potentially influential sources such as medical professionals, family, and the media represents a potentially important modifiable factor that may influence mothers' choices about infant care practices.…”
mentioning
confidence: 99%